The Beautiful Construction of Meaning In @Beauty_Byaudy's Instagram Content - Tivanka, Giza; Imawan, Khaerudin (Interaction Communication Studies Journal, 2026)
This study stems from the phenomenon of the prevalence of beauty standards on social media, which often portray women with bodies and faces considered ideal, yet these do not always align with reality. Amid this context, the Instagram account @beauty_byaudy offers a different perspective on the meaning of “beauty.” This study aims to understand how the meaning of beauty is constructed through the content posted by this account using Ferdinand de Saussure’s semiotic analysis. The study adopts a qualitative descriptive approach, with data gathered through observation, literature study, and interviews. The analysis is centered on five selected video posts, including their captions, hastags, and audience comments, to identify the meaning conveyed through visual and textual elements. The findings demonstrate a shift in the representasion of beauty, moving away from conventional ideals of physical perfection toward values such as self-acceptance, confidence, and the freedom o express oneself through makeup. In addition, the content highlights that skin conditions like acne and texture are normal and should not be stigmatized. The results indicate that the constructed meaning of beauty no longer emphasizes physical perfection but rather self-acceptance, self-confidence, and freedom of expression through makeup. These contents also affirm that conditions such as skin texture or acne are normal. This study concludes that social media can serve as a space to foster a more open and humanistic understanding of beauty. Moving forward, the research is limited in scope similar research is expected to expand the scope of study and incorporate direct perspectives from content creator.